Effects of potassium fertilization on crops yield, potassium uptake, and soil potassium fertility in rice-oilseed rape cropping systems. Issue 7 (7th June 2022) - Ye, Tinghong; Xue, Xinxin; Lu, Jianwei; Yan, Jinyao; Ren, Tao; Cong, Rihuan; Li, Xiaokun
ABSTRACT: To determine the impact of K fertilization on crop yields and soil K supplying capacity in rice ( Oryza sativa L.) and oilseed rape ( Brassica napus L.) rotation, four field experiments were conducted with five K fertilizer rates: 0 (K0), 90–147 (K1), 180–210 (K2), 270–300 (K3) and 336–390 (K4) kg K2 O ha −1 per rotation. Compared with K0, adding K increased the yield of rice and oilseed rape by 4.2–8.9% and 7.5–32.6%, respectively. Potassium fertilization increased K uptake at four sites, whereas yields remained stagnant in K2, K3, and K4 treatments despite increasing K uptake. Continuous K removal decreased soil K supplying capacity. For the 0 to 20 cm and 20 to 40 cm soil depths, the NH4 OAc-K and boiling HNO3 -K at the harvest were decreased in K0 and K1 treatments, whereas it maintained or increased in K2, K3, and K4 treatments, although negative K balances were recorded at all sites. It suggests that application 180–210 kg K2 O ha –1 in rice-oilseed rape cropping systems improved crop yield and maintained soil potassium fertility.